The General Arrangements to Borrow - Ainley, Michael (Pamphlet Series; Pamphlet Series, ;, 1984)
This paper examines the role of the IMF's first and longest-lasting borrowing arrangements, the General Arrangements to Borrow (GAB), from their inception in 1961-62 to their fundamental reform and enlargement in 1983. The General Arrangements were a product of the times. They were designed to help the IMF deal with growing strains in the par value system caused by the underlying balance-of-payments problems of the two major reserve centers, the United States and the United Kingdom. The General Arrangements were strengthened by the association of Switzerland, a nonmember of the IMF, in 1964.